Effects of Prolonged Pomace Contact on Color and Mouthfeel Characteristics in Merlot Wine During the Ageing Process Under Microwave Irradiation - Jiang-Feng Yuan; Hui-Min Qin; Li-Juan Wang; Xiao-Wen Yang; Yang Li; Ning-Bo Wan; Jie Zhang (Foods)
Wine color and mouthfeel are essential organoleptic characteristics considered by consumers. In this paper, the potential impacts on color and mouthfeel characteristics in wine, without pomace or prolonged pomace contact after different microwave treatment times, were investigated during storage. The results indicated that the trend changes in color and mouthfeel related parameters (including visible spectrum, brightness, red hue, yellow hue, color difference, saturation, hue angle, total polyphenol content, total monomer anthocyanins, total tannins, total flavan-3-ols, epigallocatechin, catechin, epicatechin, epicatechin gallate, and fluorescence spectrum) after microwave-treated and natural aged wines without pomace and prolong pomace contact were very similar. Moreover, changes in these organoleptic parameters of microwave-treated wine were faster than those of untreated wine, which required a long aging time in traditional processing. Also, microwave treatment had a long-term influence on color and mouthfeel characteristics. All these results showed that prolonged pomace contact technology could obviously improve the clarity and yellowness of wine, and microwave technology could reduce wine aging and rapidly change its color and mouthfeel characteristics. In summary, prolonged pomace contact technology is an interesting strategy to replace traditional fining agents. Microwave technology, as an efficient artificial aging technology, might reduce aging time and rapidly change organoleptic characteristics for producing high quality wine.